A novel hexagonal PtPS monolayer for high anisotropic carrier mobility and potential for photocatalytic water splitting with pronounced optical absorption - Chunying Pu; Pan Zhang; Linxuan Chen; Xindong Pan; Dawei Zhou (Scientific Reports)
Abstract Low symmetry two-dimensional noble-metal phosphochalcogenides MPX (M = Pd, Pt; X = S, Se, Te) with an unusual orthorhombic structure and pentagons attracted tremendous attention in recent years for their potential applications in optoelectronic, photocatalysts, thermoelectric devices. Motivated by the attractive properties and potential applications of MPX materials, we identified a novel stable hexagonal structure of PtPS monolayer with the space group $$P\bar {3}m1$$ using particle swarm optimization algorithms in conjunction with first-principles calculations. We not only evaluate its stability by calculations of the phonon dispersion, molecular dynamic simulation and elastic constants, but also investigate its structural, electronic, carrier mobility, optical and photocatalyst properties. The PtPS monolayer is a semiconductor with an indirect band gap of 1.23 eV (using the PBE functional) and 1.84 eV (using the HSE06 functional). More importantly, the PtPS monolayer demonstrates high electron mobility along the y direction and pronounced anisotropy, which can effectively enhance the separation of the photogenerated electrons and holes, thereby reducing recombination and improve photocatalytic activity. The photocatalytic calculations reveal that the band-edge alignments of the PtPS monolayer perfectly span the redox potential of water, providing a robust driving force for the convention of H2O into H2 and O2, making it effective in both acidic and neutral environments. Furthermore, Optical calculations demonstrate that PtPS monolayer exhibit outstanding light absorption in both visible and ultraviolet spectrum ranges, with the absorption coefficient reaching up to the order of 105 cm−1 and a high solar-to-hydrogen efficiency (16.0%). Our research suggests that the excellent properties of hexagonal PtPS monolayer can provide a guidance for experimental studies and the development of new functional layered materials based on PtPS.